Impossible nostalgia: green affect in the landscapes of the Swedish Million Programme. (19th May 2021) - Mack, Jennifer
ABSTRACT: The modernist neighbourhoods of the so-called Swedish Million Programme (1965–1974) were to house a new citizenry in utopian cities of the future, where nuclear families would live in optimal conditions and where 'rational' landscapes included playgrounds, courtyards, and traffic separation. Even so, they are 'problem areas' in current popular representations: places without history and thus unworthy of preservation. Radical proposals suggest their total demolition. Ethnographic research among residents, however, reveals alternative, multidimensional views instead. In parks, on bridges, and in tunnels, inhabitants have met friends, walked dogs, and sunbathed, often over decades. Their 'green affect' – expressed in reveries, poetry, stories, and caring suggestions for repair – challenges portrayals of the areas as disposable. Rather than suburbs without a future, residents express affection, longing, and even a seemingly impossible nostalgia for modernism's outdoor spaces. This suggests the need for preservation and the inclusion of memories and feelings in planning processes.